Antibiotic Use in Lateral Skull Base Surgery: A Survey of the North American Skull Base Society - Li, Kevin L.; Fang, Christina H.; Hawn, Vivian S.; Agarwal, Vijay; Kshettry, Varun R.; Bellile, Emily; Akbar, Nadeem A.; McKean, Erin L.; Abuzeid, Waleed M.; Moskowitz, Howard S. (Journal of Neurological Surgery Part B: Skull Base, 2021)
Objectives Antibiotic use in lateral skull base surgery (LSBS) has not been thoroughly investigated in the literature. There is wide variability in antibiotic use and insufficient data to guide management. This study aims to describe the factors and patterns influencing antibiotic use in LSBS among the membership of the North American Skull Base Society (NASBS).Design An online-based survey was designed and distributed to the membership of the NASBS. Data was analyzed using bivariate analysis and logistic regression modeling.Setting Online-based questionnaire.Participants NASBS membership.Main Outcome Measures Use of intraoperative antibiotics and use of postoperative antibiotics.Results The survey response rate was 26% (208 respondents). Of the 208 total respondents, 143 (69%) respondents performed LSBS. Most respondents are neurosurgeons (69%) with the remaining being otolaryngologists (31%). The majority of respondents (79%) are fellowship-trained in skull base surgery. Academic or government physicians make up 69% of respondents and 31% are in private practice with or without academic affiliations. Bivariate analysis showed that practice setting significantly influenced intraoperative antibiotic use (p = 0.01). Geographic location significantly affected postoperative antibiotic use (p = 0.01). Postoperative antibiotic duration was significantly affected by presence of chronic otitis media, cerebrospinal fluid leak, and surgeon training (p = 0.02, p = 0.01, and p = 0.006, respectively). Logistic regression modeling showed that the motivation to reduce infection significantly impacted postoperative antibiotic use (p = 0.03).Conclusion This study demonstrates significant variations in intraoperative and postoperative antibiotic use in LSBS among the NASBS membership. Appropriate guidelines for optimal perioperative antibiotic use patterns should be determined with randomized studies in the future.
Keywords: lateral skull base; skull base; antibiotics; prophylaxis; intraoperative; postoperative; North American Skull Base Society; NASBS